Modelling Of Compliance Behaviour Of Motorcyclists To Proper Usage Of Safety Helmets In Malaysia - Mani@Subramanian, Kulanthayan K.c (2002)
The motorcycle is a common mode of transportation in Malaysia. About 60% of fatalities and casualties resulting from road crashes in Malaysia can be attributed to the motorcycle. Half of these motorcyclist fatalities are a result of head injuries. These statistics lead to the inevitable conclusion that the head is the most important part of the body that must be protected in any injury control strategy involving motorcyclists. Studies have shown that one of the best ways to prevent head injuries is through the use of safety helmets. However, safety helmets provide protection only if used properly. Unfortunately, this is not always the case in Malaysia. Therefore, a study on the factors influencing the compliance behaviour of proper usage of safety helmets was earned out To the researcher's knowledge no such research has been undertaken in Malaysia Such a study should enable the building of a compliance behaviour model to predict the probability of riders using properly secured helmets Besides, the study looked in-depth on individual knowledge and attitude of motorcyclists toward the practice of proper use of the safety helmet The understanding of knowledge, attitude and practice is important in developing appropriate strategies for helmet usage as a person's practice can be influenced either positively or negatively through knowledge and attitude.